Greening of students' thinking as a factor in development of the textile industry - A. R. Ibatullina; I. V. Krasina; M. V. Antonova; V. V. Bronskaya; M. S. Kabysh (Юг России: экология, развитие, 2025)
Aim. Development and testing of training modules aimed at developing environmental thinking in students of textile specialties, as well as popularising the principles of "green" technologies among schoolchildren and students of secondary vocational education.The study used methods for analysing modern trends and foreign experience in the field of sustainable development of the textile industry. The introduction of electronic courses and holding Olympiads was employed to assess the level of environmental literacy of schoolchildren, students and students of secondary vocational education institutions. Pedagogical experimentation and data analysis was undertaken to assess the effectiveness of new curricula. A survey of textile industry enterprises on the topic of sustainable development of the textile industry was also undertaken.The article is devoted to the greening of educational programs for students majoring in textiles. Modern approaches to developing environmental thinking are considered and effective teaching methods and their potential impact on the transformation of the textile industry are analysed. Particular attention is paid to interdisciplinary educational practices that combine technical, environmental and social aspects of the training of future specialists. Four educational modules that meet the concept of sustainable development have been developed and implemented at the bachelor’s level in the field of "Technology and Design of Textile Products". An interregional Olympiad for schoolchildren, students and students of secondary vocational education institutions was held. An electronic course "Environmentally Safe Chemical Technologies" was developed and implemented. Articles were published in conference proceedings with the participation of students and schoolchildren, which contributed to the involvement of young people in scientific activities.The implementation of the project confirmed the effectiveness of integrating environmental modules into curricula. Students and pupils have developed a conscious attitude to the sustainable development of the textile industry.